The effect of acute equine temporomandibular joint inflammation on response to rein-tension and kinematics - Reisbig, Nathalie A.; Pifko, Justin; Lanovaz, Joel L.; Weishaupt, Michael A.; Carmalt, James L. (Frontiers in Veterinary Science, 2023)
Background: Although the temporomandibular joint (TMJ) is the major contact point between the reins in the riders’ hand, the bit in the mouth, and the rest of the horse under saddle, the role of inflammation of this joint on equine locomotion and rein tension is unknown. Objective: To determine the effect of acute TMJ inflammation on rein-tension and horse movement when horses were long-reined on a treadmill. Study design: A randomized, controlled, cross-over design. Methods: Five horses were trained by one clinician to walk and trot on a treadmill wearing long-reining equipment instrumented with a rein-tension device and reflective optical tracking markers. Subjective assessment of horse’s dominant side, and movement, were determined without rein-tension (free walk and trot); and with rein-tension (long-reined walk and trot). Continuous rein-force data from both sides were collected over ~60s from each trial. Movement was recorded using a twelve-camera optical motion capture system. One randomly assigned TMJ was subsequently injected with lipopolysaccharide and the treadmill tests repeated by investigators blinded to treatment side. A second, identical assessment was performed ten days later with the opposite TMJ being the target of intervention. Results: All horses showed reduced rein-tension on the injected, inflamed side. Increased rein-tension was required on the non-injected side at trot, to maintain them in the correct position on the treadmill post-injection. The only kinematic variable to show any significant change due to rein tension or TMJ inflammation during the walk or trot was an increase in forward head tilt in the presence of rein tension in the trot after injection. Main limitations: Low number of horses and investigation of response to acute inflammation only. Conclusions: TMJ inflammation changed, subjectively and objectively, the response to rein-input, but the horses did not become lame.